PENINGKATAN KUALITAS PEMBELAJARAN IPS MELALUI MODEL PEMBELAJARAN INKUIRI DENGAN MEDIA PAPAN PETUALANGAN - Ibrahim, Susilo, Mu'nisah, Maulana Malik (Universitas Negeri Semarang, 2013)
AbstrakTujuan penelitian ini adalah meningkatkan keterampilan guru, aktivitas siswa dan prestasi siswa dalam pembelajaran IPS kelas IV SDN Kalisalak 01 Kabupaten Batang melalui model pembelajaran inquiry dengan media papan petualangan. Penelitian ini merupakan penelitian tindakan kelas dengan tiga siklus dan dilakukan di SDN 01 Kalisalak, Kabupaten Batang. Subyek penelitian adalah guru dan siswa kelas IV. Data dikumpulkan dan dianalisis dengan menggunakan teknik analisis data kualitatif dan kuantitatif. Hasil penelitian ini menunjukkan bahwa melalui penerapan model pembelajaran inkuiri dengan menggunakan papan petualangan dapat meningkatkan kualitas pembelajaran IPS. Keterampilan guru menunjukkan persentase siklus I 59,37 % dalam kategori cukup, meningkat pada siklus II menjadi 78,12 % dalam kategori baik, dan pada siklus III persentase keberhasilan meningkat lagi menjadi 96,87 % dalam kategori sangat baik. Di sisi lain, aktivitas siswa pada siklus I persentasenya 55,56 % dengan kategori cukup, siklus II persentasenya 66,67 % dengan kategori baik, sedangkan siklus III persentase naik menjadi 83,33 % dengan kategori baik. Selain itu, ketuntasan klasikal pada siklus I 55,56 %, pada siklus kedua 72,22 %, dan meningkat pada siklus ketiga 77,78 %. Berdasarkan hasil dapat disimpulkan bahwa model pembelajaran inquiry dengan media papan petualangan dapat meningkatkan kualitas pembelajaran IPS kelas IV SDN Kalisalak 01, Kabupaten Batang.The aims of this research are to improve teachers skills, students activities and students achievement in social studies learning to the IV grade of SDN Kalisalak 01, Batang Regency through inquiry learning model by using adventureboard medium. This research is a classroom action research that is done in three cycles and conducted in SDN 01 Kalisalak, Batang Regency. The research subject is the fourth grade teachers and students. The data were collected and analyzed by using method data analysis technique of qualitative and quantitative analysis. The results of this study indicates that through the implementation of inquiry learning model by using Adventure Board medium can improve the quality of Social studies teaching and learning. The teachers' skills aspect shows that the percentage of cycle I gained 59.37% that is included enough category, the percentage of cycle II is gained 78.12% that is included good category, and in cycle III the success of percentage improves to 96.87% is included in the excellent category . On the other hand, the students activities on the the cycle I the percentage is 55.56% gains enough qualifications, the second cycle the percentage is 66.67% gains good qualification, whereas the third cycle the percentage increase to 83.33% gains good qualifications. In addition, the percentage students’ classical thoroughness study cycle I is 55.56%, while in the second cycle is 72.22%, and the third cycle increase to 77.78%. Based on the results it can be concluded that the inquiry learning model by using adventure boards medium can improve the quality of Social studies teaching and learning to the fourth grade of SDN Kalisalak 01, Kab. Batang Regency.